2020
DOI: 10.1007/s00415-020-10124-x
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barré syndrome spectrum associated with COVID-19: an up-to-date systematic review of 73 cases

Abstract: Since coronavirus disease-2019 (COVID-19) outbreak in January 2020, several pieces of evidence suggested an association between the spectrum of Guillain-Barré syndrome (GBS) and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Most findings were reported in the form of case reports or case series, whereas a comprehensive overview is still lacking. We conducted a systematic review and searched for all published cases until July 20th 2020. We included 73 patients reported in 52 publications. A broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
459
5
55

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(544 citation statements)
references
References 91 publications
25
459
5
55
Order By: Relevance
“…Although we cannot fully exclude some degree of preexisting neuropathy, lack of neuropathy in the medical history and prominent abnormal spontaneous activity in EMG suggest an acute type of neuropathy in our case series. It has already been reported that COVID-19 may be associated with the occurrence of GBS or Miller Fischer syndrome (5,(21)(22)(23). In our cases, neurological deficits were detected 4 to 5 weeks after disease onset, which may be considered rather late for GBS but more likely to result from critical illness polyneuropathy (CIP).…”
Section: Abnormal Spontaneous Activitysupporting
confidence: 50%
“…Although we cannot fully exclude some degree of preexisting neuropathy, lack of neuropathy in the medical history and prominent abnormal spontaneous activity in EMG suggest an acute type of neuropathy in our case series. It has already been reported that COVID-19 may be associated with the occurrence of GBS or Miller Fischer syndrome (5,(21)(22)(23). In our cases, neurological deficits were detected 4 to 5 weeks after disease onset, which may be considered rather late for GBS but more likely to result from critical illness polyneuropathy (CIP).…”
Section: Abnormal Spontaneous Activitysupporting
confidence: 50%
“…Searches were performed cross referencing the following key terms “Covid-19”, “Guillain Barre”, “Miller Fisher”, “GM1”, “GQ1b”, and “Ganglioside”. Of the 102 articles found eight were large scale review papers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]; the other entries were all case reports. All cases included in the eight review papers and each separate case studies were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of both the sural nerve sensory nerve action potential (SAP) and the tibial nerve compound muscle action potential (CMAP) by electroneurography measurements indicated peripheral neuropathy resulting from demyelination, typical of GBS. To date, 73 other cases of GBS have been confirmed in COVID-19 patients with male predominance around the world [ 119 123 ]. Fortunately, following immunoglobulin treatment, GBS symptoms were resolved in more than 70% of COVID-19 patients [ 123 ].…”
Section: Peripheral Nervous System-associated Comorbiditiesmentioning
confidence: 99%